THE IMPACT OF BRANDING IN B2B FINTECH INTRODUCING A NEW MODEL FOR SUCCESS FOR THE C-SUITE - Morgan, Karen (Digital Repository of Theses - SSBM Geneva, 2023)
Branding is a long-trusted strategic marketing pillar utilized by financial powerhouses like JP Morgan, Goldman Sachs, and Citibank to large fintechs like SAP, Stripe, Finastra, Fiserv, and beyond. Is a strong brand the panacea in marketing to differentiate against the competition, drive sales enablement, create a premium pricing strategy, build trust and reputation, and drive value? Present research and industry models are primarily focused on consumers and goods, which are business-to-consumer (B2C) models. Conversely, there is limited academic research on business-to-business (B2B) brand models and a lack of research on fintech brand models. B2B finance and technology are significantly more complex than B2B physical goods and industrials. The complexities include but are not limited to compliance, legal, regulatory, data privacy, data security and protection, and intricate technology systems and 24/7 support. This research suggests a seminal model based on this research’s findings. Moreover, this research will determine if there is industry value in creating the first B2B fintech brand model and how impactful it will be to fintech executives. The focus is on small to mid-sized Fintech firms defined as less than 100M USD in annual revenues. So, the primary research question to be addressed: How valuable or impactful would a new B2B fintech brand model be to the industry? The research uses the central quantitative data of, but not limited to, surveys and interviews (closed and open-ended) sourced from 30 global respondents and 10 one-on-one interviews among global fintech executives with over 500 years of experience. This research aims to advance the understanding of how the c-suite and stakeholders evaluate brand impact. Additionally, it will enable the development, adoption, and use of a new B2B fintech brand model. The research findings discovered that fintech executives believe in the value a brand model creates not only for them but for other generational fintech teams. The research, as expected, found a high level of consensus on important brand/model themes, but discovered valuable nuances and guidance. Fintech has nuances and branding has another layer of considerations in the global regions of APAC, Latin America (LatAm), and Europe, Middle East, and Asia (EMEA). The complexities of these fintech ecosystems need to be considered. Brand is the critical differentiator in these complex ecosystems. The respondents conclusively agreed on the theme of guidance and see a brand model as innovative.